An analysis of the costs of energy saving and CO2 mitigation in rural households in China. (1st November 2017) - Zhang, Weishi; Stern, David; Liu, Xianbing; Cai, Wenjia; Wang, Can
Abstract: Households may imperfectly implement energy saving measures. This study identifies two factors resulting in imperfect use of energy-saving technology by households. Households often continue to use old technologies alongside new ones, and the energy-saving technologies have shorter actual lifetimes than their designed lifetimes. These two factors are considered when computing marginal energy conservation cost and marginal CO2 abatement cost using data collected from a survey of rural households in three provinces in China. The results show that there are cost reduction for most space heating technologies, and their marginal abatement cost under full implementation ranges from −60 to 15 USD/t-CO2, while the marginal abatement cost of cooking technologies ranges from 12 to 85 USD/t-CO2 . The marginal abatement costs of the majority of technologies increased after accounting for the two implementation factors. The marginal abatement cost in the imperfect implementation scenario is higher, with a range of −1 to 15 USD/t-CO2 for space heating, and 18 to 165 USD/t-CO2 for cooking. Assuming implementation factors are constant until 2035, annually achievable CO2 abatement by 2035 is estimated to be 57, 11, and 10 Mt-CO2 /y in Hebei, Guizhou, and Guangxi Provinces. Highlights: This paper estimates energy use and CO2 abatement costs of rural residents in China. Technologies have shorter lifespans in the field than their designed lifetimes. A rural household survey was carried out in Hebei, Guizhou, and Guangxi Provinces. Marginal abatement cost of most technologies increased after accounting for the adoption efficiency and lifetime.